EVALUASI KEMAMPUAN PRODUKSI RIPPING DOZER RIPPER D375 UNTUK MENCAPAI TARGET PRODUKSI BATUBARA 180.000 TON BULAN OKTOBER DI TAMBANG AIR LAYA EXTENTION TIMUR FRONT LIMOA PT BUKIT ASAM (PERSERO) TBK UPTE: Evaluate Performance Production Of Dozer Ripper D375 To Have Coal Production Target Was 180.000 Ton On Month October In East Extention Of Tambang Air Laya Front Limoa Pt Bukit Asam (Persero) Tbk Upte) - Fredrick, Gregorius; Tono, E.P.S.B Taman; Irvani, Irvani (MINERAL, 2016)
Coal production target in East extension of TAL Limoa Front was 180.000 ton/month in October2015 but the target achieved only 115.967,59 ton with the percentage achievement of productiontarget at 64,4 %. Therefore it was necessary to evaluate performance of Dozer Ripper D375 numberseries DZ 521. The evaluation conducted by taking primer actual data in mine site such as cycletime, work distance, work effeciency, Ripper penetration and then the collecting data was processedto make reparations of DZ 521 type of D375 Ripper with the aim to meet the production target. Theachieved production after prior evaluation conducted by increasing work time effeciency was162.826,57 ton with the production achievement percentage at 90.45 % and the lack production was17.173,43 ton, a further evaluation was conducted by repairing of Ripper penetration performance andthe production was 206.138,22 ton with the production achievement percentage at 114% and theexceed production was 26138,22 ton. Then work time efficiency and Ripper penetration was improvedto obtain target production of 289.475,83 ton with the production achievement percentage at 160%and exceed production of 109.475,83 ton with time reserve 150 hours/month and 4,8 hours/daymaybe can back up the problems on location production. The evaluation had been met coalproduction target of Limoa Front.